Mechanisms for the Modulation of Dopamine D1 Receptor Signaling in Striatal Neurons - Nishi, Akinori; Kuroiwa, Mahomi; Shuto, Takahide (Frontiers in Neuroanatomy, 2011)
In the striatum, dopamine D1 receptors are preferentially expressed in striatonigral neurons, and increase the neuronal excitability, leading to the increase in GABAergic inhibitory output to substantia nigra pars reticulata. Such roles of D1 receptors are important for the control of motor functions. In addition, the roles of D1 receptors are implicated in reward, cognition, and drug addiction. Therefore, elucidation of mechanisms for the regulation of dopamine D1 receptor signaling is required to identify therapeutic targets for Parkinson’s disease and drug addiction. D1 receptors are coupled to Gs/olf/adenylyl cyclase/PKA signaling, leading to the phosphorylation of PKA substrates including DARPP-32. Phosphorylated form of DARPP-32 at Thr34 has been shown to inhibit protein phosphatase-1, and thereby controls the phosphorylation states and activity of many downstream physiological effectors. Roles of DARPP-32 and its phosphorylation at Thr34 and other sites in D1 receptor signaling are extensively studied. In addition, functional roles of the non-canonical D1 receptor signaling cascades that coupled to Gq/phospholipase C or Src family kinase become evident. We have recently shown that phosphodiesterases (PDEs), especially PDE10A, play a pivotal role in regulating the tone of D1 receptor signaling relatively to that of D2 receptor signaling. We review the current understanding of molecular mechanisms for the modulation of D1 receptor signaling in the striatum.